Effects of marine harmful algal blooms on bivalve cellular immunity and infectious diseases: A review. (July 2020) - Lassudrie, Malwenn; Hégaret, Hélène; Wikfors, Gary H.; da Silva, Patricia Mirella
Abstract: Bivalves were long thought to be "symptomless carriers" of marine microalgal toxins to human seafood consumers. In the past three decades, science has come to recognize that harmful algae and their toxins can be harmful to grazers, including bivalves. Indeed, studies have shown conclusively that some microalgal toxins function as active grazing deterrents. When responding to marine Harmful Algal Bloom (HAB) events, bivalves can reject toxic cells to minimize toxin and bioactive extracellular compound (BEC) exposure, or ingest and digest cells, incorporating nutritional components and toxins. Several studies have reported modulation of bivalve hemocyte variables in response to HAB exposure. Hemocytes are specialized cells involved in many functions in bivalves, particularly in immunological defense mechanisms. Hemocytes protect tissues by engulfing or encapsulating living pathogens and repair tissue damage caused by injury, poisoning, and infections through inflammatory processes. The effects of HAB exposure observed on bivalve cellular immune variables have raised the question of possible effects on susceptibility to infectious disease. As science has described a previously unrecognized diversity in microalgal bioactive substances, and also found a growing list of infectious diseases in bivalves, episodic reports of interactions between harmful algae and disease in bivalves have been published. Only recently, studies directed to understand the physiological and metabolic bases of these interactions have been undertaken. This review compiles evidence from studies of harmful algal effects upon bivalve shellfish that establishes a framework for recent efforts to understand how harmful algae can alter infectious disease, and particularly the fundamental role of cellular immunity, in modulating these interactions. Experimental studies reviewed here indicate that HABs can modulate bivalve-pathogen interactions in various ways, either by increasing bivalve susceptibility to disease or conversely by lessening infection proliferation or transmission. Alteration of immune defense and global physiological distress caused by HAB exposure have been the most frequent reasons identified for these effects on disease. Only few studies, however, have addressed these effects so far and a general pattern cannot be established. Other mechanisms are likely involved but are under-studied thus far and will need more attention in the future. In particular, the inhibition of bivalve filtration by HABs and direct interaction between HABs and infectious agents in the seawater likely interfere with pathogen transmission. The study of these interactions in the field and at the population level also are needed to establish the ecological and economical significance of the effects of HABs upon bivalve diseases. A more thorough understanding of these interactions will assist in development of more effective management of bivalve shellfisheries and aquaculture in oceans subjected to increasing HAB and disease pressures. Graphical abstract: Image 1 Highlights: Review of the main studies on effects of marine harmful algae on bivalve immune cells (hemocytes) and on infectious disease. Harmful algae can modulate host-pathogen interactions in bivalves on various way (increase or decrease the infection). Some experimental studies report the involvement of cellular immunity and global physiological weakness in the modulations. Other mechanisms possibly involved: HAB effects on bivalve filtration; direct interaction of HABs with pathogens. Future research recommendations: field studies, at the population level, to establish the ecological and economical significance.